Postbloom Fruit Drop (PFD) Identification and Management - Megan M. Dewdney; Natalia A. Peres; Jamie D. Burrow (EDIS)
This 2-page publication is a minor revision written by Megan M. Dewdney, Natalia A. Peres, and Jamie D. Burrow, and published by the Plant Pathology Department, July 2019.